A unified rock deformation model incorporating the development of unique strain energy method (USEM) and normalised stress-strain path criterion / Ahmad Fadzil Jobli - Jobli, Ahmad Fadzil (2022)
Weathering of rocks in a wet tropical climate gives a significant impact on the disintegration and the strength reduction of rock. Researchers have proposed various methods to express rock deformation characteristics, however, due to different nature and complex formulation, these criteria are not easy to be employed. The most common approach has neglected to account for the role of shear strength properties, a shortcoming addresses by this thesis. Moreover, there is an almost complete lack of data in the literature considering the impact of weathering on a tropical granitic rock, which necessitates further laboratory work on rock triaxial test, including basic mechanical properties, shear strength, and stress-strain analysis. Therefore, this study aims to fill these research gaps and produce a unified rock deformation model that can characterize the complete shear strength and stress-strain behaviour of tropical granitic weathered rock under any confining effect. This can be achieved by innovating a single stress strain UCS data to project a complete deformation characteristic in terms of the shear strength model and stress-strain model. The normalised strain – rotational multiple yield surface framework (NS-RMYSF) was utilised to evaluate the intrinsic shear strength properties. At the same time, a spreadsheet program was designed to analyse the nonlinear H-B failure criterion. Then, the stress-strain predictive model applying NS RMYSF and H-B material constant, mb was developed. A new simplification was then introduced to improve the stress-strain model that is known as normalised stress-strain path criterion. However, these criteria are fully dependent on the peak stress and peak strain prediction. Therefore, a unique strain energy method (USEM) was proposed to infer the relationship between the stress, strain, and total strain energy, UT. The development of UT was observed based on stress-strain trapezoidal rules and the potential of USEM was investigated. The results and analysis confirm that single UCS data can be used to demonstrate the independent shear strength model, mb using the proposed USEM parameters. Also, the proposed USEM relationships can be used to predict the peak stress and peak strain that significantly contribute to the development of an independent stress-strain model based on the proposed normalised stress-strain path criterion. The developed and validated shear strength model and stress-strain model were further verified against other rock types to check their reliability. Finally, the complete unified rock deformation model was conclusively established as the model was improvised in terms of additional parameters that can be used to suit any deformation characteristic of any rock type. The most influential finding and contribution of this study is the ability to utilise single UCS stress-strain data to predict complete shear strength and stress-strain profile irrespective of any confining pressures. It is very significant to researchers, consultants, and engineers as it informs our theoretical understanding regarding the importance of stress-strain as the most powerful and basic fundamental in rock deformation analysis. The role of possible intrinsic shear strength interaction and the innovative unique strain energy method (USEM) were also highlighted as the main knowledge contribution.